(3GdbjO GdeJYdb HeTQhYjI GdOdjd Hjf MeGjI GdMbhb GdaQOjI h eQGYGI eUdMI GdeLJeY ai GdELQGAGJ GdLfGFjI GdebGQfI (B/ s - (3NGdO YHOGdMejO Ydi NVQs; (3CMeO YhV HdGds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2019)
(3Ef MQjI GdEKHGJ GdLfGFj JYfj GdMQjI GdcGedI aj Jchjf GdCOdI(B: (3h efGbTJgG h GdGbJfGY HgG TQjWI Cf jchf Pdc ai MOhO GdbGfhf(B. (3h MQjI GdEKHGJ dG JYfj EWdGbgG Ohf MOhO(B: (3h dG jLhR GdeRL Hjf WQb GdEKHGJ GdJj Jchf eUOkQG ddOdjd h Hjf GdMOhO GdhGLH eQGYGJgG YfO LeY gPg GdCOdI(B: (3h efGbTJgG hJbjjegG(B: (3cd Pdc dG HO hCf jJe aj OGFQI GdTQYjI cCSGS bGfhfj ddEKHGJ(B. (3h jXgQ eHOC GdEKHGJ GdLfGFj hGVkMG aj eQGMd Jchjf GdOdjd h efGbTJg h Jbjjeg HhGSWI GdeMceI(B. (3aJWHjb eHOC MQjI GdEKHGJ GdLfGFj aj cGaI GdfUhU GdefXeI dELQGAGJ LeY GdGSJOdGdGJ h ELQGAGJ GdJMbjb GdGHJOGFi h ELQGAGJ GdeMGceI(B. (3h aj eQMdI efGbTI GdOdjd(B: (3afLO eHOC MQjI GdEKHGJ jJLdi aj GdfUhU GdebQQI eHOC TahjI GdeQGaYI MJi jSJWjY GdNUhe efGbTI COdI GdOYhi GdeYQhVI(B: (3h eHOC GdehGLgI Hjf GdNUhe GdPj jbQQ MVhQ GdNUhe CKfGA ELQGAGJ GdJMbjb(B: (3eG de JJWdH GdVQhQI ZjQ Pdc(B: (3Ch MGdI GdGSJYLGd(B: (3h cGaI GdfUhU GdBNQI GdebQQI Mb GdOaGY(B. (3h aj eQMdI Jbjje GdCOdI GdebOeI aj GdOYhi fLO eHOC MQjI GdEKHGJ HJWHjbg aj GdfUhU GdJj JbVj HCf jMce GdbGVj aj GdOYhi MSH YbjOJg GdJj JchfJ dOjg HMQjJg GdcGedI(B: (3h Cf GdbGVj dG jLH Cf jMce HfGA Ydi Cj Odjd de ojWQM CeGeg aj GdLdSI(B: (3h Cf GdeMceI ZjQ ebjOI HeG Je JOhjfg aj GdJMbjb GdGHJOGFj h eMGVQ LeY GdGSJOdGdGJ(B: (3EdG EPG bVi GdbGfhf HNdGa Pdc(B. (3h Jedc GdeMceI SdWI EfJGL GdOdjd aj eQMdI GdJMbjb GdfgGFi GdPi jLQi YfO fXQ GdOYhis
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFis
(3HHdjhLQGajG(B: (3UaMGJ (B335-360s
Keywords: (3eGgjI GdOdjd hCSS bhGYO GdEKHGJ GdLfGFis; (3bGYOI eTQhYjI JMUjd GdGOdI hSdWGJ eGehQ GdVHW GdbVGFis; (3GdYjhH GdJi JYJhQ GdOdjd hJHWdgs; (3GdYjhH GdJi JeS MQeI LSe GdGfSGfs; (3GdEcQGg s; (3GdJYPjHs; (3GdbHV Ydi GdGaQGO hMHSge Ohf hLg Mbs; (3GdYjhH GdJi JeS MQeI eScf GdGfSGf heSJhOY GSQGQgs; (3GdJaJjT s; (3GdJUfJ Ydi GdGJUGdGJ hGdQSGFds; (3bjO eTQhYjI GdOdjd hGdYOGdI GdeGehdIs; (3GdebJQMGJ GdeWQhMI Ydi bjO GdeTQhYjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs